1999
DOI: 10.3109/09513599909167578
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y, leptin, galanin and insulin in women with polycystic ovary syndrome

Abstract: It has been reported that polycystic ovary syndrome (PCOS) is very frequently associated with obesity, insulin resistance and hyperinsulinemia. However, metabolic disorders may lead to suppression of reproductive hormone secretion during undernutrition and in obesity. Some neuropeptides, such as neuropeptide Y (NPY) and galanin, modulate the control of appetite and play an important role in the mechanism of luteinizing hormone-releasing hormone (LHRH) secretion. NPY and galanin regulate appetite via both centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 26 publications
8
43
0
1
Order By: Relevance
“…However in severely obese, polycystic ovarian syndrome (PCOS) patients it has been observed that this inverse relationship between leptin and NPY is lost. NPY levels are often elevated, yet some PCOS patients exhibit equal to or higher than expected leptin levels likely due to endocrine dysregulation [41][42][43] which is consistent with our observations in this study. Furthermore, NPY response to ghrelin is also defective in PCOS patients [41].…”
Section: Doi: 107243/2050-0866-2-23supporting
confidence: 91%
See 1 more Smart Citation
“…However in severely obese, polycystic ovarian syndrome (PCOS) patients it has been observed that this inverse relationship between leptin and NPY is lost. NPY levels are often elevated, yet some PCOS patients exhibit equal to or higher than expected leptin levels likely due to endocrine dysregulation [41][42][43] which is consistent with our observations in this study. Furthermore, NPY response to ghrelin is also defective in PCOS patients [41].…”
Section: Doi: 107243/2050-0866-2-23supporting
confidence: 91%
“…NPY levels are often elevated, yet some PCOS patients exhibit equal to or higher than expected leptin levels likely due to endocrine dysregulation [41][42][43] which is consistent with our observations in this study. Furthermore, NPY response to ghrelin is also defective in PCOS patients [41]. This evidence, taken together with our current study, suggests a general uncoupling of hormonal feedback mechanisms.…”
Section: Doi: 107243/2050-0866-2-23supporting
confidence: 91%
“…In this context our recent data from a study comprising of 2 groups of overweight insulin-resistant PCOS women [150] showed that a 3-month treatment with metformin (Group 1) and rosiglitazone (Group 2), added to an oral hormone contraceptive (OHC) (a standard combination of ethynil oestradiol 35 g plus cyproterone acetate 2 mg) resulted in decrease of atherogenic adipocytokines (leptin, resistin, and TNF ) ( Table 2) that may have beneficial effects in the future prevention of atherosclerosis and cardiovascular diseases in this risk cohort of young women. But the serum concentrations of NPY also decreased that is in support of some our previous [151] and other authors [143,144] data for impaired NPYleptin link in PCOS. The change of NPY and adipocytokines was associated with weight loss only in the metformin group that is an expected effect of the drug and in conformity with other studies [150].…”
Section: Npy and Reproductive Functionsupporting
confidence: 91%
“…The increase in NPY in their study was independent of the increase in BMI. In obese women with PCOS, plasma leptin was increased compared to lean women [143]. Bidzińńska-Speichert et al [144] also found higher leptin and NPY levels and lower galanin levels in PCOS women as compared to healthy controls [144].…”
Section: Npy and Reproductive Functionmentioning
confidence: 92%
See 1 more Smart Citation